2018
DOI: 10.1002/ajmg.a.9
|View full text |Cite
|
Sign up to set email alerts
|

Schuurs‐Hoeijmakers syndrome in two patients from Japan

Abstract: Schuurs‐Hoeijmakers syndrome is a rare disease characterized by intellectual disability and dysmorphic facial features among various physical abnormalities due to PACS1 mutation. To date, 28 patients with a recurrent de novo PACS1 mutation (c.607C > T) have been reported, primarily in Western populations. Here, we describe two Japanese patients with Schuurs‐Hoeijmakers syndrome with a recurrent PACS1 mutation. In addition to the typical clinical symptoms, each patient presented novel clinical phenotypes. One p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…SHMS or PACS1 Neurodevelopmental disorder was first reported in 2012 and it is a rare cause of ID. Likely, many patients still remain unreported and, although more than 150 patients are currently known, only 61 patients have been published up to date [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 9 , 10 , 11 , 12 , 14 , 16 ]. The disease causing PACS1 variant always occurred de novo and therefore was excluded in the unaffected analyzed parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHMS or PACS1 Neurodevelopmental disorder was first reported in 2012 and it is a rare cause of ID. Likely, many patients still remain unreported and, although more than 150 patients are currently known, only 61 patients have been published up to date [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 9 , 10 , 11 , 12 , 14 , 16 ]. The disease causing PACS1 variant always occurred de novo and therefore was excluded in the unaffected analyzed parents.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients had anomalies in the eyes, nose, heart, and gastrointestinal system. After this first review, further patients were reported mainly from series of patients with ID evaluated through massive paralleled sequencing studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Remarkably, almost all patients show the same heterozygous de novo PACS1 variant c.607C > T that results in exchange of an arginine residue to a tryptophan at position 203 and is assumed to be a gain of function variant.…”
Section: Introductionmentioning
confidence: 99%
“…PACS1 and PACS2 are two human paralogous genes that each cause a distinctive human disorder. A specific class of mutations in PACS1 , that is, c.607C > T p.(Arg203Trp) and c.608G > A p.(Arg203Gln), results in Schuurs‐Hoeijmakers syndrome (OMIM #615009), characterized by intellectual disability and facial dysmorphism (Dutta, 2019; Hoshino et al, 2019; Pefkianaki et al, 2018; Schuurs‐Hoeijmakers et al, 2012; Schuurs‐Hoeijmakers et al, 2016; Stern et al, 2017). Meanwhile, a specific class of mutations in PACS2 , that is, c.625G > A p.(Glu209Lys) and c.631G > A p.(Glu211Lys), causes early infantile epileptic encephalopathy 66 (EIEE 66) (OMIM #618067) (Olson et al, 2018; Terrone et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They also delineated the clinical characteristics of all the patients and suggested that this variation in PACS1 defines a recognizable syndromic form of DD/ID and dysmorphic facial features ( Schuurs-Hoeijmakers et al, 2016 ). Subsequently, there have been sporadically reported cases with the same de novo mutation (c.607C > T) in PACS1 that caused ID and distinctive facial features ( Gadzicki et al, 2015 ; Stern et al, 2017 ; Martinez-Monseny et al, 2018 ; Pefkianaki et al, 2018 ; Wang et al, 2018 ; Dutta, 2019 ; Hoshino et al, 2019 ; Kurt Colak et al, 2020 ), except another novel variation (c.608G > A) which affects the same amino acid (Arg203; Miyake et al, 2018 ). As reviewed and reported recently, more than 50 cases with SHMS have been described in the literature, and all of them have DD/ID and dysmorphic facial features, including 51 postnatal individuals and three prenatal cases ( Kurt Colak et al, 2020 ; Lusk et al, 2020 ; Seto et al, 2020 ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%